Does Workplace Stress Mediate The Effects of Job Insecurity and Toxic Workplace Environment on Turnover Intention? - Safitri, Intan; Pareke, Fahrudin JS (Gorontalo State University, 2026)
This study examines the influence of job insecurity and toxic workplace environment on turnover intention, with workplace stress serving as a mediating variable among retail employees. The research is motivated by the high turnover rates commonly found in the retail sector, which are often associated with unstable employment conditions and unfavorable work environments. Using a quantitative approach, primary data were collected through online questionnaires from 302 Indomaret employees in Bengkulu City. The data were analyzed using SmartPLS 4.0 to assess the validity, reliability, and structural relationships among the variables. The findings indicate that job insecurity has a direct and significant positive effect on turnover intention, suggesting that uncertainty regarding job stability increases employees’ desire to leave the organization. While a toxic workplace environment does not directly influence turnover intention, it significantly increases workplace stress, which in turn positively affects turnover intention. Moreover, workplace stress is found to mediate the relationships between job insecurity and turnover intention, as well as between toxic workplace environment and turnover intention. Overall, the study highlights the crucial role of workplace stress as a psychological mechanism linking unfavorable work conditions to employees’ intention to leave, offering important implications for employee retention strategies in the retail sector.